2017
DOI: 10.1037/ocp0000026
|View full text |Cite
|
Sign up to set email alerts
|

Work-related self-efficacy as a moderator of the impact of a worksite stress management training intervention: Intrinsic work motivation as a higher order condition of effect.

Abstract: Employees with low levels of work-related self-efficacy may stand to benefit more from a worksite stress management training (SMT) intervention. However, this low work-related self-efficacy/enhanced SMT benefits effect may be conditional on employees also having high levels of intrinsic work motivation. In the present study, we examined this proposition by testing three-way, or higher-order, interaction effects. One hundred and fifty-three UK government employees were randomly assigned to a SMT intervention gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 65 publications
2
57
0
5
Order By: Relevance
“…The specific nature of training in effective studies was diverse: problem solving (Ayres & Malouff, 2007;Varekamp et al, 2011), psychological flexibility (Biglan et al, 2013), sleep training (Ebert et al, 2015), happiness training (Feicht et al, 2013), mindfulness approaches (Flaxman & Bond, 2010a, 2010bMcGarrigle & Walsh, 2011), cognitive behavioural therapy [CBT] (Kojima et al, 2010;Proudfoot, Corr, Guest, & Dunn, 2009), stress management (Lloyd et al, 2016;Umanodan, Shimazu, Minami, & Kawakami, 2014), resilience training (Mache et al, 2015), meditation awareness training (Shonin et al, 2014), relaxation training (Taniguchi et al, 2007), psychosocial skills training (Traeger et al, 2013), empowerment (Whiteside et al, 2006) and coping skills (Williams et al, 2009). The diversity of approaches reporting positive effects suggests that the particular focus of this kind of training is not that important.…”
Section: Personal Resources Interventionsmentioning
confidence: 99%
“…The specific nature of training in effective studies was diverse: problem solving (Ayres & Malouff, 2007;Varekamp et al, 2011), psychological flexibility (Biglan et al, 2013), sleep training (Ebert et al, 2015), happiness training (Feicht et al, 2013), mindfulness approaches (Flaxman & Bond, 2010a, 2010bMcGarrigle & Walsh, 2011), cognitive behavioural therapy [CBT] (Kojima et al, 2010;Proudfoot, Corr, Guest, & Dunn, 2009), stress management (Lloyd et al, 2016;Umanodan, Shimazu, Minami, & Kawakami, 2014), resilience training (Mache et al, 2015), meditation awareness training (Shonin et al, 2014), relaxation training (Taniguchi et al, 2007), psychosocial skills training (Traeger et al, 2013), empowerment (Whiteside et al, 2006) and coping skills (Williams et al, 2009). The diversity of approaches reporting positive effects suggests that the particular focus of this kind of training is not that important.…”
Section: Personal Resources Interventionsmentioning
confidence: 99%
“…Employees believing that their work and efforts make sense, are worthwhile and pay off will experience positive emotional states (Elovainio et al, 2015;Tummers & Den Dulk, 2013), report higher intrinsic motivation (Lloyd, Bond, & Flaxman, 2017), job satisfaction (Steger, Littman-Ovadia, Miller, Menger, & Rothmann, 2013) and personal accomplishment (Maslach, 2011).…”
Section: Hypothesis 1amentioning
confidence: 99%
“…As outlined in Frankl's meaning-centered concept of logotherapy and existential analysis (Frankl, 1963), perceived meaningfulness about one's own work buffers stress, reduces vulnerability for emotional exhaustion (Tummers & Den Dulk, 2013), and predicts occupational well-being (Bano, 2014;Frankl, 2014). Optimistic, self-efficacious employees who perceive their work as meaningful, are more likely to achieve their goals at work, and to do so more efficiently (Lloyd et al, 2017;Xanthopoulou, Bakker, Demerouti, & Schaufeli, 2009).…”
Section: Moderating Role Of Meaningfulness On Maladaptive Coping Dumentioning
confidence: 99%
“…Therefore, the following hypotheses were proposed: Jurnal Pengurusan 57(2019), Galley Proof ISSN 0127-2713 and MyCite Indexes 7 H3 Work-family conflict has a negative influence on emotional well-being THE MEDIATING EFFECT OF PROBLEM-FOCUSED COPING BETWEEN WORK-FAMILY CONFLICT AND WELL-BEING OUTCOMES Lazarus and Folkman (1984) reported that workers can possess the capability to handle challenging situations, control stress, demands, and solve problems and/or with positive thinking and emotional expression, to manage stressful circumstances. For instance, Lloyd, Bond and Flaxman (2017) stated that problem-focused coping was more effective in handling work-related stressors. Likewise, Ding et al (2015) discovered that problem-focused coping is applied more often to manage daily work problems.…”
Section: Work-family Conflict and Emotional Well-beingmentioning
confidence: 99%